2019
DOI: 10.1007/s00035-019-00230-6
|View full text |Cite
|
Sign up to set email alerts
|

Dieback and expansions: species-specific responses during 20 years of amplified warming in the high Alps

Abstract: The largest alpine–nival vegetation permanent plot site in the Alps, the GLORIA mastersite Schrankogel (Tirol, Austria), provided evidence of warming-driven vegetation changes already 10 years after its establishment in 1994. Another decade later, in 2014, substantial compositional changes with increasing ratios of warmth-demanding to cold-adapted species have been found. The current study deals with species-specific responses involved in an ongoing vegetation transformation across the alpine–nival ecotone on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 51 publications
8
27
0
Order By: Relevance
“…These observed decreases in plant cover on siliceous bedrock go in line with findings at Mt Schrankogel, the largest permanent plot site in the alpine-nival ecotone of the Alps on siliceous bedrock, where vascular plant cover also decreased over the last 20 years (Lamprecht et al, 2018). There, the decrease was mainly caused by a cover decrease of the cold-adapted species (Steinbauer et al, 2020), while new species from lower elevations were not able to fill the open gaps. Vascular plant cover changes, therefore, may not necessarily be connected to the worldwide observed increase of species richness on summits (Dullinger et al, 2007;Pauli et al, 2012;Steinbauer et al, 2018).…”
Section: Bedrock Specific Surface Cover Characteristics and Changes Over Timesupporting
confidence: 83%
See 1 more Smart Citation
“…These observed decreases in plant cover on siliceous bedrock go in line with findings at Mt Schrankogel, the largest permanent plot site in the alpine-nival ecotone of the Alps on siliceous bedrock, where vascular plant cover also decreased over the last 20 years (Lamprecht et al, 2018). There, the decrease was mainly caused by a cover decrease of the cold-adapted species (Steinbauer et al, 2020), while new species from lower elevations were not able to fill the open gaps. Vascular plant cover changes, therefore, may not necessarily be connected to the worldwide observed increase of species richness on summits (Dullinger et al, 2007;Pauli et al, 2012;Steinbauer et al, 2018).…”
Section: Bedrock Specific Surface Cover Characteristics and Changes Over Timesupporting
confidence: 83%
“…Species distribution models predict drastic losses of such coldadapted species by the end of the 21st century (Dirnböck et al, 2011;Engler et al, 2011;Dullinger et al, 2012). Recent studies in the Central Austrian Alps have already shown losses and decrease in cover of cold-adapted species from permanent plots (Lamprecht et al, 2018;Steinbauer et al, 2020). However, species distribution models might overestimate losses, as extinctions are still rarely encountered in revisitation studies in the European Alps (Kulonen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the situation in the central Alps, where accelerating thermophilisation occurred with progressing losses of vegetation cover over a 20-year period (Lamprecht et al 2018), thermophilisation in Sierra Nevada resulted from slightly stronger losses of cold-adapted than gains of warmth-demanding species. In the high central Alps, however, this was far more pronounced with strong and consistent losses of all subnival-nival species (Steinbauer et al 2020). Periods without signals of thermophilisation (2004( /2006-2015, in contrast, showed increases of total species cover.…”
Section: Changes In Cover and Community-weighted Thermic Indicatormentioning
confidence: 96%
“…Rumpf et al (2018) reported from the Alps that the trailing lower margins of species ranges are contracting at least as rapidly as the leading edges are expanding towards higher elevations. In the central Alps, cold-adapted species, being restricted to the high-elevation zones, have experienced strong losses in cover in the lower part of their distribution range (Lamprecht et al 2018;Steinbauer et al 2020). In the Sierra Nevada, endemic species disappeared significantly more often than more widespread species.…”
Section: Colonisation and Disappearance Eventsmentioning
confidence: 99%
“…For the most part, this is because the climate envelope for many mountain species is expected to shrink and, in some regions, disappear entirely as a consequence of increased global temperatures (Halloy & Mark 2003;La Sorte & Jetz 2010;Freeman et al 2018). While range contractions have already been observed in some mountain plants (Grabherr et al 1994;Lenoir et al 2008;Steinbauer et al 2020) and animals (Freeman et al 2018, Wilson et al 2005, not all species are responding to climate change in the same way (Lenoir et al 2010;Tingley et al 2012;Gibson-Reinemer & Rahel 2015). What remains unclear is the capacity of mountain species to adapt (Hargreaves et al 2014;Michalet et al 2014;Normand et al 2014;Louthan et al 2015), and the characteristics that allow species to persist in the face of a changing climate (Fordham et al 2012;Foden et al 2018).…”
Section: Introductionmentioning
confidence: 99%